The Validity of Mathematics Learning Model Based on Realistics Mathematics Education and Literacy in SMP - ., Rusdi; Made Arnawa, I; Fauzan, Ahmad; ., Lufri (KnE Social Sciences, 2023)
This study aims to determine the validity of the Mathematics Learning Model Based on Realistic Mathematics Education and Literacy that has been developed. This type of research is the Plomp model design research which consists of three stages, namely preliminary research, the development or prototype stage, and the assessment stage. The model developed produces products that are documented in book form, namely model books, hypothetical learning trajectories, teacher books, and student books. The validity of the developed model is investigated at the prototype stage. The data in this study are the results of the experts’ assessment of the four products. Data collection techniques using a questionnaire. The data collection instruments in this study were model book validation sheets, hypothetical learning trajectory sheets, teacher book validation sheets, and student book validation sheets. The data obtained were analyzed using descriptive statistical techniques. The results of the data analysis show that the Mathematics Learning Model based on Realistic Mathematics Education and Literacy developed meets the valid criteria. Keywords: Learning model; mathematics education; realistic mathematics